THE CASE STUDY OF INDONESIA’S EMISSION TRADING SYSTEM AND LESSONS LEARNED FOR VIETNAM - Huyen, Nguyen Thi Thanh; Chau, Nguyen Minh; Thao, Do Thu; Anh, Dang Chau (Graduate Program of Universitas Tarumanagara, 2024)
Climate change has increasingly become a concerning threat in the past few decades. Aware of this reality, developing nations are actively engaged to mitigate greenhouse gas emissions. One of these engagements is the implementation of emmission trading system. This article aims to compare the effectiveness of Indonesia's and Vietnam’s expected emmission trading system to propose policy implications for Vietnamese governments. By using the desk study through analyzing and synthesizing documents, the authors conduct the assessment of these two emmission trading systems against five criteria: environmental effectiveness, economic efficiency, market management, revenue management, and stakeholder engagement. The recent implementation of emmission trading system in Indonesia demonstrates that most criteria are evaluated at low and medium levels and some of them do not have already available data for research. Similarly, Vietnam’s expected emmission trading system has little information to analyze. From the research results, the paper proposes several market management features that can be applied in the context of Vietnam.